Novel glycovariant biomarkers of CA125 and CA15-3 and their diagnostic performance across histotypes of ovarian cancer: A multi-cohort study in Sweden and Finland - Roos Alexander, Hanna; Jain, Shruti; Gidwani, Kamlesh; Ulfenborg, Benjamin; Ottander, Ulrika; Lundin, Eva; Hynninen, Johanna; Afrin Ruma, Shamima; Huhtinen, Kaisa; Sundfeldt, Karin; Pettersson, Kim; Idahl, Annika (Elsevier Ireland Ltd., 2025)
Objective
To evaluate diagnostic accuracy of novel nanoparticle immunoassays across different histotypes of tubo-ovarian carcinoma (TOC) at diagnosis.
Method
This multicenter observational study consisted of consecutive patients (n = 1,312) having surgery due to suspected ovarian pathology. Serum were analyzed with Sialyl-Thomsen-nouveau (STn) antibody and Macrophage-Galactose-Lectin (MGL) for the detection of cancer antigen 125 (CA125) and 15-3 (CA15-3) glycoforms using CA125 enzyme immunoassay (EIA), CA15-3EIA and HE4EIA as references. Receiver operating characteristics (ROC) were applied and sensitivity at 75 % and 98 % specificity were calculated across histotypes.
Result
TOC was present in 596 patients and 716 had benign disease. CA125STn showed higher sensitivity at 98 % specificity compared with CA125EIA for high grade serous ovarian carcinoma (HGSC) (0.85 vs 0.62, p < 0.001), HGSC early-stage (0.66 vs 0.24, p = 0.003), and HGSC late-stage (0.90 vs 0.69, p < 0.001). CA15-3STn showed higher sensitivity at 98 % specificity compared to CA125EIA for mucinous ovarian carcinoma (0.50 vs 0.16, p = 0.038). No improvements were found for low grade serous carcinoma (LGSC), endometrioid and clear cell histotypes. The best performing combined biomarker test was CA125STn + HE4EIA with higher sensitivity at 98 % specificity for HGSC (0.93 vs 0.86, p < 0.001) and HGSC late-stage (0.97 vs 0.91p < 0.001) compared with CA125EIA + HE4EIA.
Conclusion
The STn glycovariants of CA125 and CA15-3 have improved sensitivity at high specificity for high grade serous and mucinous ovarian carcinoma and often perform better than the commonly used biomarker CA125EIA.